2022
DOI: 10.3390/antibiotics11111564
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Study of Chromosomally and Plasmid-Mediated Multidrug Resistance and Virulence Determinants in Klebsiella Pneumoniae Isolates Obtained from a Tertiary Hospital in Al-Kharj, KSA

Abstract: Klebsiella pneumoniae is an emergent pathogen causing respiratory tract, bloodstream, and urinary tract infections in humans. This study defines the genomic sequence data, genotypic and phenotypic characterization of K. pneumoniae clinically isolated from Al-Kharj, KSA. Whole-genome analysis of four K. pneumoniae strains was performed, including de novo assembly, functional annotation, whole-genome-phylogenetic analysis, antibiotic-resistant gene identification, prophage regions, virulent factor, and pan-genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The lowest co-existence patterns were bla TEM+SHV & bla CTX-M+TEM+SHV represented by K. pneumoniae (6.67%) and E. coli (3.82%) respectively. Similarly, the highest co-existence of the gene bla CTX-M+TEM (21%) was found in the ESBL E. coli & K. pneumoniae from Qatar [59], Saudi Arabia [45, 69] and followed by the least co-existence of the genes bla TEM+SHV, bla CTX-M+SHV & bla CTX-M+TEM+SHV were detected in their same studies, but in contrast, the Moglad et al , Badger-Emeka et al and Sid Ahmed et al found that the highest co-harbored genes were bla CTX-M+TEM+SHV (50% & 24.7%), bla CTX-M+SHV (50% & 10.1%) found in the E. coli , K. pneumoniae and other Enterobacterales in their studies. [70,71] Likewise, the lowest co-expression of the genes bla TEM+NDM , bla TEM+IMP and bla CTX-M+TEM+SHV+IMP were also detected in 2.22% K. pneumoniae, 5% P. aeruginosa and 10% of each A. baumannii to each gene combination.…”
Section: Discussionmentioning
confidence: 99%
“…The lowest co-existence patterns were bla TEM+SHV & bla CTX-M+TEM+SHV represented by K. pneumoniae (6.67%) and E. coli (3.82%) respectively. Similarly, the highest co-existence of the gene bla CTX-M+TEM (21%) was found in the ESBL E. coli & K. pneumoniae from Qatar [59], Saudi Arabia [45, 69] and followed by the least co-existence of the genes bla TEM+SHV, bla CTX-M+SHV & bla CTX-M+TEM+SHV were detected in their same studies, but in contrast, the Moglad et al , Badger-Emeka et al and Sid Ahmed et al found that the highest co-harbored genes were bla CTX-M+TEM+SHV (50% & 24.7%), bla CTX-M+SHV (50% & 10.1%) found in the E. coli , K. pneumoniae and other Enterobacterales in their studies. [70,71] Likewise, the lowest co-expression of the genes bla TEM+NDM , bla TEM+IMP and bla CTX-M+TEM+SHV+IMP were also detected in 2.22% K. pneumoniae, 5% P. aeruginosa and 10% of each A. baumannii to each gene combination.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the horizontal transfer of mobile genetic elements carrying resistant determinants to several antimicrobial types is the major driver of resistance in gram-negative bacteria 24 . Today, more than 100 acquired resistance genes have been identified in Klebsiella strains, conferring the susceptibility of wide ranges of antimicrobial agents 2 , 25 . This corroborates the need to continue molecular epidemiology studies to assess the resistance genotypes and their diversity and distribution in each region 8 .…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to those reported from the eastern region of the country where the proportions of resistance were more than 70% for ampicillin, amoxicillin/clavulanic acid, amoxicillin/clavulanic acid, ceftriaxone and cefuroxime 11 . In addition, a study indicated that K. pneumoniae has become resistant to third-generation cephalosporins and carbapenems, which led to narrowing therapeutic choices for MDR K. pneumoniae infection 2 . The high resistance rates could be explained by these antibiotics being the most prescribed therapeutic agents in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations